Konsep Kesatuan Tubuh Kristus Berdasarkan Efesus 4:1-6 Terhadap Peningkatan Jumlah Remaja Yang Datang Beribadah Di Gereja Bethel Indonesia Tarisi - Tamoes, Titus; Sailendra , Arthinda Arthur (JURNAL KADESI, 2023)
Diversity is not something to justify a division. It is in diversity that the positive values developed in social life arise. According to researchers' observations in the field of a church, unity among the congregation members is not well embedded. The church is dominated by a certain ethnicity. This condition creates problems in the spiritual life of adolescents, faced with the hours of worship, the church atmosphere that creates satiety, between them, so that it boosts the passive attitude among them to invite others to worshipping in the church. The study uses the Qualitative Research Method and the researchers titled the study, The Concept of the Unity of the Body of Christ Based on Ephesians 4:1-6 has a positive influence on the increase in the number of teenagers who come to worship. The concept of the unity of the body of Christ is an appropriate and effective way of guiding and building young people in a better direction so that young people can grow to the maturity of faith through the involvement of young children in the communion of worship in the church based on Ephesians 4:2. First, teenagers already have the basic knowledge of humility, gentleness and patience and learn to apply it in their lives. Secondly, adolescents understand what is understood as a form of unity: one body, one Spirit, one hope, one Lord, one faith, one baptism, one God and one Father. Thirdly, the presence of teenagers in worship indicates an increase in quantity and begins to be involved in the restriction of spiritual service. Being humble one to another, not selfish, but one with one another, as members of the body of Christ.